Using Borehole Temperatures for Knowledge Transfer about Mountain Permafrost: The Example of the 35-year Time Series at Murtèl-Corvatsch (Swiss Alps) - Wilfried Haeberli; Jeannette Noetzli; Daniel Vonder Mühll (Revue de géographie alpine)
Climate-related permafrost is widespread in cold mountains and heavily affects slope stability. As a subsurface phenomenon, however, it is often still absent in the perception of key partners concerning the discussion and anticipation of long-term impacts on high mountain regions from continued global warming. Outreach and knowledge transfer, therefore, play a key role. Long-term observations of permafrost temperatures measured in boreholes can be used to convey answers and key messages concerning thermal conditions in a spatio-temporal context, related environmental conditions, affected depth ranges, and impacts of warming and degradation on slope stability.The 35-year Murtèl-Corvatsch time series of borehole temperatures from which data is available since 1987, is used here as an example. Today, mountain permafrost is well documented and understood regarding involved processes, as well as its occurrence in space and evolution in time. Thermal anomalies caused by global warming already now reach about 100 meters depth, thereby reducing the ground ice content, causing accelerated creep of ice-rich frozen talus/debris (so-called “rock glaciers”) and reducing the stability of large frozen bedrock masses at steep icy faces and peaks.